Effects of a new approach of aerobic interval training on cardiac autonomic modulation and cardiovascular parameters of metabolic syndrome subjects - Vanzella, Lais Manata [UNESP] (2019)
Objective: To evaluate the effects of 16 weeks of periodized aerobic interval training (AIT) on cardiac autonomic modulation and cardiovascular parameters of metabolic syndrome (Mets) individuals. Subjects and methods: The sample was composed of 52 subjects with a diagnosis of Mets, allocated into two groups: AIT (AITG; n = 26) and control (CG; n = 26).The AITG was submitted to a periodized AIT program, over 16 weeks, while CG was not submitted to any training program. To evaluate the autonomic modulation and cardiovascular parameters in both groups, heart rate variability (HRV) indices, blood pressure (BP), and heart rate (HA) were measured at the beginning and end of the training. Results: Statistically significant differences were not observed in HFms(2) (high frequency in milisseconds), LFnu (low frequency in normality unit), HFnu (high frequency in normality unit), and LF/HF ratio indices, or in the cardiovascular parameters BP and HR when comparing the AITG with the CG. However, significant increases in rMSSD (root-means square differences of successive R-R intervals), LFms(2) (low frequency in milliseconds), and SDNN (standard deviation of normal to normal intervals) were observed in the AITG. Conclusion: Periodized AIT promoted positive effects on autonomic modulation of Mets subjects, characterized by an increase in the parasympathetic, sympathetic, and global modulation of this population. Additionally, cardiovascular parameter alterations were not observed in Mets subjects submitted to periodized AIT.